Orthodox monasticism past and present - McGuckin, John Anthony (Gorgias Eastern Christianity studies, 2015)
Pt. 1: Ancient Christian ascetical theology. Embodying tradition, seeking transformation: glimpsing asceticism(s) in the New Testament / Karri L. Whipple -- Monasticism in the Christian East: an introduction / J. A. McGuckin -- 'Taking upon the likeness of angels': asceticism as the angelical life in Aphrahat's Demonstrations / Sujit T. Thomas -- The recitation of the psalms among early Christian ascetics / Jill Gather -- The virgins sing orthodoxy: Ephrem's choirs & the dissemination of Nicene thought in Syria / Robert Najdek -- The power to curse and the power to save: the monk, the prophet & the story of Elisha's curse of the She Bears (2 Kings 2:23-24) / Revd. Mary Julia Jett -- Rhetoric and the monastic rule in Byzantium: from anchoritism to coenobitism / Julia Khan -- The devil in the desert / Kevin McKeown -- An ancient ascetical drama of woman and the dragon: Perpetua's rise into the animus-world / Jeff Pettis -- The pure 'eye of her soul': the asceticism of the deaconess Olympias as reflected in the writings of the Fathers / V. K. McCarty -- Evagrius Ponticus, the Origenian ascetic (and not the Origenistic 'heretic') / Ilaria L. E. Ramelli -- Asceticism through the lens of anthropology: the Greek Fathers from Justin to Gregory Nazianzen on the soul and the holy spirit / Vicki Petrakis -- St. Shenoute of Atripe and his monastic order / Deaon Antonios the Shenoudian (A. Bibawy) -- Hagiographic traditions of Ethiopian monasticism / Atsede Maryam Elegba -- The evolution of fundamental Christological elements in the works of St. Cyril of Alexandria / Vasily Novikov -- Humanity's reconciliation with the divine through the mystery of the Incarnation of the Word in the thought of St. Isidore of Pelusium & St. Cyril of Alexandria / Eirini Artemi -- The monk as mourner: St. Isaac the Syrian & monastic identity in the 7th C. & beyond / Hannah Hunt -- The dying church: hierarchy as self-sacrifice in Pseudo-Dionysius / Kate McCray -- Plotinus and the essence - energeia distinction: a Neoplatonic influence on Dionysius Areopagita / Joshua Packwood -- Maximos and neurobiology: a neurotheological investigation of asceticism as erosion of the passions & the gnomic will / Luis Joshua Sales -- Converting the use of death: the ascetic theology of St. Maximus the Confessor in Ad Thalassium 61 / Gregory Tucker -- The monk philosopher in Yahya ibn 'Adi (d.974) and Severus Ibn al-Muqaffa' (d. c. 987) / Zachary Ugolnik -- What is the 'breath of God'? - bibliographic theology in Armenian history from Astvacashuntch to St. Grigor Narekatsi's The Book of Sadness / Anthony J. Elia -- A royal family: the significance of Saint Sava and his parents for the establishment of Serbian monasticism and the Serbian church / V Rev. Zivojin Jakovljevic -- The 15th century Typikon of Neilos Damilas for the convent of the mother of god on Venetian-Crete / Mary McCarthy -- Pt. 2: Monastic reflection and modernity. Contemporary monasticism: why join a monastery? / Metropolitan Jonah (Paffhausen) -- A triptych of contemporary Romanian spiritual elders / His Grace the Rt. Revd. Dr. Macarie Dragoi -- The beauty of silence in Christian monastic tradition / Teodor Damian -- The 'mystical mundane' in Fr. Nikon of Karoulia's letters to Gerald Palmer / Christopher D. L. Johnson -- Purifying the heart in order to see: praxis and perception in Dostoevsky's Brothers Karamazov / Tea Jankovic -- The centrality of St. Isaac the Syrian's ascetical theology in Dostoevsky's The Brothers Karamazov / Rico Monge -- Engaged monasticism: Mother Maria Skobtsova and twenty-first century American Orthodox monasticism / Fr. Peter M. Preble -- Psychic crisis in monastic communities: the ascetical writings of Evagrius of Pontus in the light of modern understandings / John L. Grillo -- Markets and monasticism: a survey & appraisal of Eastern Christian monastic enterprise / Dylan Pahman -- Spiritual warfare and the struggle for apatheia / Theodore Grey Dedon -- The concepts of time as applied to monasticism & asceticism / Nicholas Samaras